1996
DOI: 10.1037/0893-164x.10.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Asking questions about urges or cravings for cigarettes.

Abstract: Smokers (N = 116) were administered the Questionnaire of Smoking Urges (QSU; S. T. Tiffany & D. J. Drobes, 1991) to explore the measurement of drug urges or cravings. Confirmatory factor analysis replicated the 2-factor structure, using the 6 best items on each of the QSU factors, although further analyses indicated that 1 conceptual factor may be a better fit. Three different categories of internally consistent items were identified within the QSU: urges to smoke, expectancies from smoking, and intentions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
104
1
7

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 57 publications
2
104
1
7
Order By: Relevance
“…It is possible that the original two-factor structure reported by Tiffany and Drobes (1991) and replicated by Davies et al (2000) cannot be confirmed with older, treatment-seeking individuals who have been smoking larger quantities of cigarettes over a longer period of time. It will be important for future studies to test whether or not this original two-factor structure using all 26 items can be confirmed in such samples.In the present study, an alternative model, initially proposed by Kozlowski et al (1996), using the 12 most robust items from the original analysis appeared to represent an adequate fit for the data. Structural equation models, because they are merely an approximation of reality, are not generally expected to fit the data perfectly (Floyd & Widaman, 1995).…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…It is possible that the original two-factor structure reported by Tiffany and Drobes (1991) and replicated by Davies et al (2000) cannot be confirmed with older, treatment-seeking individuals who have been smoking larger quantities of cigarettes over a longer period of time. It will be important for future studies to test whether or not this original two-factor structure using all 26 items can be confirmed in such samples.In the present study, an alternative model, initially proposed by Kozlowski et al (1996), using the 12 most robust items from the original analysis appeared to represent an adequate fit for the data. Structural equation models, because they are merely an approximation of reality, are not generally expected to fit the data perfectly (Floyd & Widaman, 1995).…”
mentioning
confidence: 68%
“…To address this problem, several studies have developed longer urge scales with as few as 5 items or as many as 30 items, using more traditional psychometric approaches (e.g., Flannery, Volpicelli, & Pettinati, 1999;Tiffany, Singleton, Haertzen, & Henningfield, 1993). These scales, designed to assess either a single unidimensional factor (e.g., the Penn Alcohol Craving Scale; Flannery (Cox, Tiffany, & Christen, 2001;Kozlowski et al, 1996). Therefore, a questionnaire that is short enough for practical use but long enough to provide a reliable measure of craving is ideal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations